1998
DOI: 10.1105/tpc.10.2.135
|View full text |Cite
|
Sign up to set email alerts
|

The AmMYB308 and AmMYB330 Transcription Factors from Antirrhinum Regulate Phenylpropanoid and Lignin Biosynthesis in Transgenic Tobacco

Abstract: MYB-related transcription factors are known to regulate different branches of flavonoid metabolism in plants and are believed to play wider roles in the regulation of phenylpropanoid metabolism in general. Here, we demonstrate that overexpression of two MYB genes from Antirrhinum represses phenolic acid metabolism and lignin biosynthesis in transgenic tobacco plants. The inhibition of this branch of phenylpropanoid metabolism appears to be specific to AmMYB308 and AmMYB330, suggesting that they recognize their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
350
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 488 publications
(366 citation statements)
references
References 65 publications
15
350
0
1
Order By: Relevance
“…It suggested that maize provided a possible model system to examine the hypothesis that the expansion of MYB gene family was associated with the regulation of novel plant cellular functions. MYB340 (Moyano et al 1996), MYB308 and MYB330 (Tamagnone et al 1998) were reported to be other MYB genes involved in phenylpropanoid metabolism. The Arabidopsis TRANSPARENT TESTA (TT2) gene encoded an R2R3 MYB domain protein that acted as a key determinant for proanthocyanidin accumulation in developing seed (Nesi et al 2001).…”
Section: Phenylpropanoid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…It suggested that maize provided a possible model system to examine the hypothesis that the expansion of MYB gene family was associated with the regulation of novel plant cellular functions. MYB340 (Moyano et al 1996), MYB308 and MYB330 (Tamagnone et al 1998) were reported to be other MYB genes involved in phenylpropanoid metabolism. The Arabidopsis TRANSPARENT TESTA (TT2) gene encoded an R2R3 MYB domain protein that acted as a key determinant for proanthocyanidin accumulation in developing seed (Nesi et al 2001).…”
Section: Phenylpropanoid Metabolismmentioning
confidence: 99%
“…The inhibition of this branch of phenylpropanoid metabolism was found to be specific to AmMYB308 and AmMYB330, suggesting that they recognized their normal target genes in these transgenic plants. Experiments with yeast indicate that AmMYB308 can act as a very weak transcriptional activator and overexpression competitively inhibited the activity of stronger activators recognizing the same target motifs (Tamagnone et al 1998). …”
Section: Phenylpropanoid Metabolismmentioning
confidence: 99%
“…This plant-specific TF family is defined by a common DNA-binding domain of two repeats of about 50 amino acids. Examination of R2R3MYB TFs by phylogenetic analysis has revealed functionally distinct subgroups (Stracke et al, 2001;Jiang et al, 2004;Dubos et al, 2010), of which several are involved in the regulation of particular branches of phenylpropanoid metabolism; for example, anthocyanin production (PazAres et al, 1987;Quattrocchio et al, 1998;Schwinn et al, 2006), phlobaphene biosynthesis (Grotewold et al, 1994), flavonol biosynthesis (Mehrtens et al, 2005), hydroxycinnamic acid biosynthesis (Tamagnone et al, 1998;Jin et al, 2000), and monolignol biosynthesis (Zhou et al, 2009;Zhong et al, 2010). In legumes, there is an extra dimension to the regulatory control of phenylpropanoid metabolism because they produce isoflavonoids that serve as phytoalexins and as signaling molecules for nodulation (Subramanian et al, 2007).…”
mentioning
confidence: 99%
“…During the terminal stage of electron transfer, there are not only COX that can activate oxygen, but also other oxidases such as PPO and alternative oxidases that can react with oxygen (Elthon and McIntosh, 1986;Tamagnone et al, 1998). Studies have shown that thiourea is an inhibitor of copper-containing oxidases, including PPO (Dubios and Erway, 1946).…”
Section: Discussionmentioning
confidence: 99%
“…Improper oxidation of these intermediates may affect the synthesis of colored pigments (Winkel-Shirley, 2001). Furthermore, the phenylpropanoid pathway also results in biosynthesis of lignins (Tamagnone et al, 1998;Hoffmann et al, 2004). Therefore, if the synthesis of these two biomolecules is affected, fiber cell development can certainly be impacted.…”
Section: Discussionmentioning
confidence: 99%